Specific intercellular binding of the β-amyloid precursor protein to the presenilins induces intercellular signaling: Its significance for Alzheimer’s disease - Dewji, Nazneen N. (The National Academy of Sciences, 1998)
Genetic evidence has implicated three proteins, the β-amyloid precursor protein (β-APP) and the two homologous presenilins (PS-1 and PS-2), in the etiology of Alzheimer’s disease (AD). How these three proteins jointly contribute to AD, however, is not clear. Nor is any of their normal physiological functions known. Herein, we demonstrate, confirming a prediction made earlier, that β-APP and either PS-1 or PS-2 act as a specific membrane-bound ligand binding intercellularly with either of its two membrane receptors. This results in a cell–cell adhesion, after which rapid transient increases in protein tyrosine kinase activity and protein tyrosine phosphorylation occur coordinately inside one or both of the two adherent cells. The spectrum of proteins modified by tyrosine phosphorylation differs depending on whether PS-1 or PS-2 is involved in the specific intercellular binding to β-APP, which implies that PS-1 and PS-2 have distinct, rather than redundant, functions in normal physiology. The relevance of this intercellular interaction and signaling process to AD is discussed.